Weather signature of “El Niño” in western Mexico - César O. Monzón; Anatoliy E. Filonov; Irina E. Tereshchenko; Arturo Figueroa M. (Geofísica Internacional, 2003)
The study focuses on the signature of “El Niño” on temperature and precipitation in Guadalajara, Manzanillo, Guanajuato, Mexicali and Ensenada, Mexico. The water level of Lake Chapala reflects to some extent the integral processes in temperature and precipitation within the Lerma-Chapala watershed. Hidden periodicities in the monthly time series included peaks of 0.5 to 22 years in the normalized spectra of temperature and precipitation oscillations, with confidence limit above 90%. Within the 2-22 years range, the periods of 2 to 7 years can be related to “El Niño” phenomenon. The periods of 9 to 22 years may be related to solar influence. Hourly measurements of temperature, relative humidity, speed and wind direction were used to study “El Niño” in Guadalajara. During “El Niño” year, there were a large number of hours recording temperatures over 25°C. Higher than normal temperatures were recorded from the beginning of March 1998. Low humidity values, less than 30%, were evident from late January till June of the same year. During this time, the wind showed a West-North-West steady direction, with speeds of up to 9 m/s.